The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/21568235.2017.1296367
|View full text |Cite
|
Sign up to set email alerts
|

Individuals in action: bringing about innovation in higher education

Abstract: This article addresses academics who innovate in higher education and their characteristics. We undertake a qualitative case study of six individuals who implemented disruptive and transformative pedagogical approaches and curricular practices in their departments and/or at their institutions. Our findings point to six common characteristicsmotivation to change institutionalized practices, interest in change, experience in the field, multiembeddedness, authority to act, and the strategic use of social networks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 62 publications
(58 reference statements)
2
37
0
3
Order By: Relevance
“…A large-scale study conducted in the higher education context (S. Manca & Ranieri, 2016a) cited the lack of time, the lack of administrative support, and the increase in workload as being some of the barriers that hinder the usage of social media. This situated HEIs as inhibitors rather than facilitators of technology adoption (Hasanefendic et al, 2017). For example, the findings by Corcoran and Duane (2018) found that knowledge sharing on social media platforms are limited due to the prevalent organization structure and culture in higher education.…”
Section: Discussionmentioning
confidence: 99%
“…A large-scale study conducted in the higher education context (S. Manca & Ranieri, 2016a) cited the lack of time, the lack of administrative support, and the increase in workload as being some of the barriers that hinder the usage of social media. This situated HEIs as inhibitors rather than facilitators of technology adoption (Hasanefendic et al, 2017). For example, the findings by Corcoran and Duane (2018) found that knowledge sharing on social media platforms are limited due to the prevalent organization structure and culture in higher education.…”
Section: Discussionmentioning
confidence: 99%
“…Many innovations in education do not result into the desired changes. Next to institutional factors, teachers' behaviour to cope with innovations is of utmost importance for understanding the success or failure of innovations (Hasanefendic et al, 2017). Teachers play a crucial role in innovations (George & Sabapathy, 2011;Koeslag-Kreunen, Van der Klink, Van den Bossche & Gijselaers, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of an institutional entrepreneur focuses on the role of HEIs as a change agent which participates in the designing of a particular institutional arrangement through involving different strategies (organizing sufficient resources and mobilizing resources and power) to enact the institutional changes [7][8][9], and the new role makes HEIs more socially responsible. Merton et al [10] examined the impact of changing of curriculum (in two US universities) and found that implementation of changed learning processes and curriculum was influenced by how well the changes in learning processes are associated with the arrangements and culture of the institutions, which directly have an impact on the success of innovation [10,11]. In another study on educational system transformation, Furst-Bowe [12] strongly suggests the need for a system thinking approach for changing the HEIs' educational programs, learning processes, strategy, and management [12].…”
Section: Introductionmentioning
confidence: 99%
“…In order to create successful innovation, HEIs depend on its social networking capabilities such as how they collect resources, facilitate the knowledge dissemination process, and identify opportunities by forming social ties [11,13], thus increasing legitimacy for collective action and social innovation process. Social innovation in HEIs usually comes as a consequence of collective action and collaboration with institutional actors of the innovation ecosystem [14,15], low level of collaboration reduce the chances of co-development and co-creation of social innovation (CoSoI).…”
Section: Introductionmentioning
confidence: 99%